Effect of temperature, pH, and oxygen level on the multiplication of naturally occurring Legionella pneumophila in potable water. - Wadowsky, R M (1985)
A water culture containing naturally occurring Legionella pneumophila and associated microbiota was maintained in the laboratory by serially transferring the culture in tap water which had been sterilized by membrane filtration. Successful maintenance of the water culture depended upon transferring the culture when the growth of L. pneumophila was in the late-exponential to early-stationary phase. The water culture was used as a source of naturally occurring bacteria to determine some of the parameters which affect the multiplication of L. pneumophila in tap water. Naturally occurring L. pneumophila multiplied at a temperature between 25 and 37 degrees C, at pH levels of 5.5 to 9.2, and at concentrations of dissolved oxygen of 6.0 to 6.7 mg/liter. Multiplication did not occur in tap water which contained less than 2.2 mg of dissolved oxygen per liter. An association was observed between the multiplication of L. pneumophila and the non-Legionellaceae bacteria which were also present in the water culture. The method of preserving naturally occurring L. pneumophila and associated microbiota may facilitate studies on the symbiosis of L. pneumophila with other microorganisms.